2013
DOI: 10.1136/thoraxjnl-2013-204457.105
|View full text |Cite
|
Sign up to set email alerts
|

S98 Vitamin D deficiency increases bacterial load in a murine model of sepsis-induced lung injury: Abstract S98 Table 1.

Abstract: Ageing is associated with increased episodes of sepsis and poorer outcomes. Statins are associated with improved outcomes during infection. We aimed to characterise the impact of age and acute severe infection on key neutrophil functions, assess whether physiologically relevant doses of simvastatin altered neutrophil functions and if benefits were seen, when during a septic episode statins could be utilised. Methods Neutrophils from healthy volunteers and patients with lower respiratory tract infections (LRTI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research from Professor McAuley's group (Belfast) investigated the use of a novel inhaled domain antibody to TNFR1 in a human model of lung injury induced by inhaled lipopolysaccharide (LPS)25 and the role of targeting Siglec-E receptors on activated macrophages with polymeric nanoconstruct surface-functionalised with sialic acid targeting moieties 26. Additionally, work from Dr Thickett's group (Birmingham) showed that vitamin D deficiency increases the bacterial load in the bronchoalveolar lavage fluid and blood of mice following caecal-ligation and puncture27 and that neutrophils in the elderly have normal phagocytic ability but their migratory ability is impaired 28. The migratory accuracy could be restored with simvastatin, but unfortunately this modulatory effect was not seen in neutrophils from septic patients.…”
Section: Critical Carementioning
confidence: 99%
“…Research from Professor McAuley's group (Belfast) investigated the use of a novel inhaled domain antibody to TNFR1 in a human model of lung injury induced by inhaled lipopolysaccharide (LPS)25 and the role of targeting Siglec-E receptors on activated macrophages with polymeric nanoconstruct surface-functionalised with sialic acid targeting moieties 26. Additionally, work from Dr Thickett's group (Birmingham) showed that vitamin D deficiency increases the bacterial load in the bronchoalveolar lavage fluid and blood of mice following caecal-ligation and puncture27 and that neutrophils in the elderly have normal phagocytic ability but their migratory ability is impaired 28. The migratory accuracy could be restored with simvastatin, but unfortunately this modulatory effect was not seen in neutrophils from septic patients.…”
Section: Critical Carementioning
confidence: 99%